Exploring counter-theoretical instances of graduate learners’ self-regulatory processes when using an online repository - Shaikh, Kamran; Zuberi, Amna; Venkatesh, Vivek (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2012)
Academic self-regulation theories have proposed that learning involves a complex set of cognitive and metacognitive mechanisms that are enacted in phases. These phases include task understanding, strategy adoption, monitoring, and reflection. Whereas classical approaches to self-regulation contend that these phases work together to influence academic performance, the empirical research reported herein reveals that, for essay writing in an online learning environment, improved self-regulation is not necessarily associated with improved learning outcomes. We begin by reviewing frameworks for academic self-regulation, specifically in the context of learners’ experiences in online repositories equipped with Topic Maps (ISO 13250) indexes. We then offer explanations for counter-theoretical interactions found between task understanding (a frontline phase of self-regulation) and academic performance in 38 graduate learners who used Topic Maps to tackle ill-structured essay tasks. Our investigation sheds light not only on how learners’ perceptions of feedback facilitate task understanding, but also on the complex relationship between task understanding and monitoring proficiencies.